2010
DOI: 10.4141/cjps08233
|View full text |Cite
|
Sign up to set email alerts
|

Impact of production practices on fiber yield of oilseed flax under Canadian prairie conditions

Abstract: . 2010. Impact of production practices on fiber yield of oilseed flax under Canadian prairie conditions. Can. J. Plant Sci. 90: 61Á70. Flax (Linum usitatissimum L.) cultivars commonly grown in western Canada have been developed primarily for seed production. These cultivars tend to be shorter, have lower fibre content, and have lower above-ground biomass than cultivars developed specifically for fibre production. Linseed production is the dominant flax product in western Canada and fibre is a co-product of oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The stem accumulated a large amount of P postanthesis, indicating that the stem has strong P demand (more discussion below). Irvine et al (2010) showed that the stems of oilseed flax contained high fiber content. This supports the results of our study to some extent, which found that stem DM and P accumulation in the stem increased by maturity.…”
Section: P Accumulation and Partitioningmentioning
confidence: 99%
“…The stem accumulated a large amount of P postanthesis, indicating that the stem has strong P demand (more discussion below). Irvine et al (2010) showed that the stems of oilseed flax contained high fiber content. This supports the results of our study to some extent, which found that stem DM and P accumulation in the stem increased by maturity.…”
Section: P Accumulation and Partitioningmentioning
confidence: 99%
“…Both types can serve as feedstock for the production of biomass energy in the biofuel industry (Naik et al, 2010 ). Most varieties are either oilseed or fiber types as opposed to dual purpose (Deyholos, 2006 ) but the intermediate type opens the door for development of a true dual purpose flax (Irvine et al, 2010 ) where both stems and seeds have commercial outcomes (You et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…2002; Diederichsen & Ulrich 2009; Irvine et al . 2010). Without needing to satisfy textile quality standards, fibre yield as a by-product could integrate with linseed cultivation income, thus making the crop more attractive to Italian growers.…”
Section: Introductionmentioning
confidence: 99%